Structural evolution of the amorphous grain boundary phase during nanocrystallisation of Fe 72 Cu 1 Nb 4.5 Si 13.5 B 9 - Principi, Guido Mariano (2004)
The structure of the amorphous grain boundary phase during progressive stages of nanocrystallisation in the Fe 72 Cu 1 Nb 4.5 Si 13.5 B 9 alloy has been followed using XRD, SAXS and Mössbauer spectroscopy. The initial compositional inhomogeneity sets-in with increasing crystallisation, as a result of the depletion in Fe of the amorphous phase, which partly homogenises for longer annealing times due to long-range diffusion. © 2003 Elsevier B.V. All rights reserved.